2018
DOI: 10.1371/journal.pmed.1002713
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a text-messaging-based smoking cessation intervention (“Happy Quit”) for smoking cessation in China: A randomized controlled trial

Abstract: BackgroundChina has the highest global prevalence of cigarette smokers, accounting for more than 40% of the total cigarette consumption in the world. Considering the shortage of smoking cessation services in China, and the acceptability, feasibility, and efficacy of mobile-phone-based text messaging interventions for quitting smoking in other countries, we conducted a mobile-phone-based smoking cessation study in China.Methods and findingsWe conducted a randomized controlled trial in China across 30 cities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
95
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 34 publications
(48 reference statements)
5
95
2
5
Order By: Relevance
“…According to the Pew Research Center, the vast majority of Americans—95%—own a cell phone, and an estimated 98% of all cell phones have texting capabilities (17,37). Evidence-based SMS interventions for health behavior include smoking cessation, primary care attendance, breast cancer screening, and sun safety, among others (20,22,23,2731). However, minimal research has been conducted applying SMS interventions to CC screening, and no prior research, apart from this study, has targeted a CC prevention intervention by leveraging the universal health care access setting of the ED.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Pew Research Center, the vast majority of Americans—95%—own a cell phone, and an estimated 98% of all cell phones have texting capabilities (17,37). Evidence-based SMS interventions for health behavior include smoking cessation, primary care attendance, breast cancer screening, and sun safety, among others (20,22,23,2731). However, minimal research has been conducted applying SMS interventions to CC screening, and no prior research, apart from this study, has targeted a CC prevention intervention by leveraging the universal health care access setting of the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Short message service (SMS) on mobile phones, also known as text messaging, is a low-cost, scalable, and effective means of delivering health behavior interventions and could be used to reinforce health messages initially delivered in the acute context of the ED (1226). Evidence-based SMS interventions for health behavior include smoking cessation, primary care attendance, breast cancer screening, and sun safety, among others (20,22,23,2731).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that giving health warning messages that fit smokers’ personal circumstances and psychological factors can effectively affect smokers’ subjective beliefs about the harms of smoking, which in turn would affect their intentions and decisions 35 36. Relative counselling should be adopted to help smokers to deal with adverse reactions during smoking cessation, such as nicotine withdrawal, which may obstruct their persistence to quit,37 and psychosocial interventions should be provided to help them to cope with mood problems and to enhance external self-efficacy to resist temptation and social influences 38…”
Section: Discussionmentioning
confidence: 99%
“… 6 Our previous randomised controlled trial (RCT) of text-messaging-based smoking cessation intervention (‘Happy Quit’) has shown an increased biochemically verified continuous smoking abstinence at week 24 from around 2% to more than 6%. 7 The provision of more comprehensive interventions, such as widely accessible online treatment strategy for smoking cessation, might further increase the quitting rates.…”
Section: Introductionmentioning
confidence: 99%